The Logical Theory of Evidence-Based Interpretation (Scientific Source Analysis) - Ilkhomov, Z.A. (Universitas Muhammadiyah Sidoarjo, 2020)
Today the greatest role in historical processes is played by sources and their data, and also at the logical scientific conclusions which based on drawn sources with the corresponding purposes. This article shows the basic points of view in the field of methodology of historical science and work with sources in historical researches and on the basis of interpretation of the facts logically suitable opinions on the given question are stated.